Relationship Between Explosive Strength Characteristics with Change of Direction Speed in Junior and Cadet Karate Athletes - Herrera-Valenzuela, T (IOS Press BV, 2022)
BACKGROUND: Explosive strength and change of direction speed (CODS) are relevant physical abilities in karate. OBJECTIVE: To examine the relationship between the characteristics of explosive strength and the 5-m linear sprint (5M) with CODS performance and ii) to examine the influential characteristics of explosive strength on CODS performance. METHODS: Eighteen cadet and junior karate athletes, eight females and ten males were evaluated. The physical abilities assessments included: squat jump (SJ), countermovement jump (CMJ), 5M and CODS. Also, pre-stretch percentage increase (PSA), eccentric utilization index (EUR) reactive strength index (RSI) were calculated. RESULTS: Superior performance (p< 0.05) was documented in SJ, CMJ and CODS in male vs. female. Also, significant correlations between CODS with SJ and CMJ (r=-0.70 to -0.80; R2=-0.51 to -0.73; p< 0.05, respectively) and correlations (r=-0.14 to -0.22; R2= 0.01 to 0.04; p> 0.05) between CODS with RSI, EUR and PSA. Multiple regression model documented that only SJ significantly influenced CODS performance in male (R2= 60%; p= 0.009) and female (R2= 71%; p= 0.001). CONCLUSION: CODS correlate with SJ and CMJ. In particular, SJ influence CODS independently of gender. © 2022 - IOS Press. All rights reserved.